On the Influence of Production Technologies and Savings Propensities on Economic Growth. Findings Considering a Solow's Type Growth Model - Grassetti, Francesca (Frontiers in Applied Mathematics and Statistics, 2019)
This review analyses the influence of technologies and saving propensities of workers and shareholders on economic growth, considering the \cite{bk2000} model. We show how investing behaviours and production peculiarities condition the evolution of capital over time. We highlight that fluctuations and multiple equilibria arise only when the elasticity of substitution between capital and labour is lower than one. Moreover, only production functions with variable elasticity of substitution between inputs are able to describe the poverty trap phenomenon. Complex dynamics emerge when the difference between the saving propensity of the two income groups is sufficiently high.